1999
DOI: 10.1007/s004010051008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple system atrophy with remarkable frontal lobe atrophy

Abstract: The autopsy findings of a multiple system atrophy (MSA) patient with remarkable frontal lobe atrophy are described. The patient was a 65-year-old woman with a 13-year history of untreatable parkinsonism, dysautonomia and progressive motor aphasia. The brain weight was 810 g, and there was remarkable atrophy of the cerebrum predominantly in the frontal lobe, striatum, pons and cerebellum. Microscopic examination revealed a preserved cortical structure with laminar gliosis in the sixth layer of the precentral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 16 publications
1
51
0
1
Order By: Relevance
“…Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27]. Pathological studies evaluating neuronal morphology in detail and distribution of GCIs have provided evidence of cortical involvement especially in the frontal cortex and its associated white matter as well as in the striatum of patients with MSA, suggesting that GCIs in these areas may contribute to cognitive deficits [15,24]. Recent longitudinal and voxel-based MRI studies additionally supported the notion of cortical involvement in patients with MSA, demonstrating widespread cortical atrophy of the frontal, parietal, and insular areas [3,14,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27]. Pathological studies evaluating neuronal morphology in detail and distribution of GCIs have provided evidence of cortical involvement especially in the frontal cortex and its associated white matter as well as in the striatum of patients with MSA, suggesting that GCIs in these areas may contribute to cognitive deficits [15,24]. Recent longitudinal and voxel-based MRI studies additionally supported the notion of cortical involvement in patients with MSA, demonstrating widespread cortical atrophy of the frontal, parietal, and insular areas [3,14,21].…”
Section: Discussionmentioning
confidence: 99%
“…Kawai et al [12] recently reported that the severity of frontal cognitive impairments in patients with MSA was significantly correlated with hypoperfusion in the frontal or prefrontal cortex, postulating that frontal lobe involvement may be responsible for cognitive dysfunction in patients with MSA. Additionally, frontal type cognitive dysfunctions in patients with MSA may be associated with subcortical cognitive dysfunctions secondary to striatal or subcortical white matter pathology [4,15,17]. Furthermore, Beyer et al [2] reported that WMH was more severe in patients with Parkinson's disease (PD) dementia compared with those with non-demented PD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some cases of MSA were reported to have cerebral cortical atrophy with white matter involvement [100,101,102,103,104]. The main pathological change comprised cell loss and gliosis in the putamen, substantia nigra, locus ceruleus, inferior olives, pontine nuclei, cerebellar Purkinje cells, and intermediolateral cell columns of the spinal cord [105].…”
Section: Multiple System Atrophymentioning
confidence: 99%
“…Hence in MSA, the substantia nigra, striatum, inferior olivary nucleus, pontine nuclei, and cerebellum are affected [18,49,105]. In some cases, there may be progressive cerebral atrophy affecting the frontal lobes [103] and the motor/ premotor areas [168], the limbic system also being affected, principally in longer duration cases [138]. Although MSA is regarded as a single entity, two main subtypes are now recognized [72], viz., the cerebellar subtype (MSA-C) and parkinsonian subtype (MSA-P).…”
Section: Disorders: Ad -Alzheimer's Disease Agd -Argyrophilic Grain mentioning
confidence: 99%
“…A close association between GCI and microtubules has also been demonstrated [129], aberrant or ectopic expression of cdk5 and MAPK leading to abnormal phosphorylation of microtubule cytoskeletal proteins and the formation of inclusions. In MSA cases with frontal lobe atrophy [103], there are cell losses in laminae V/VI of the cerebral cortex, and GCI are often found in white matter. In addition, inclusions are found in the granule cell layer of the dentate gyrus and pre-frontal cortex and 'dot-like' structures or grains in the PHG [4].…”
Section: Cellsmentioning
confidence: 99%